Functional Design and Route Planning Decisions for Adaptive UAVs in Multi-Objective Inspection Scenarios of Overhead Transmission Lines - Feng, Yanbin; Zhang, Hairuo; Jing, Cheng (IEEE International Conference on Power, Intelligent Computing and Systems (Online), 2023)
With the large-scale popularization of UHV AC/DC transmission projects in China, the transmission corridors spanning multiple regions are the links connecting the power grids of various regions, and ensuring the reliable operation of overhead transmission lines is of great significance to safeguard the national economy. Therefore, this paper proposes a functional design and route planning decision scheme for adapting UAVs in overhead transmission line multi-target inspection scenarios. First, a three-dimensional model of the airborne LiDAR, the external environment (field, mountain, forest), and the environment through which the overhead transmission line passes is established, second, the dynamic A* algorithm is used for global planning of the UAV flight route in this environment, and finally, path smoothing is performed by using B spline curves to obtain a flyable path that satisfies the UAV flight constraints. The simulation results show that the proposed strategy can well simulate the UAV path planning in multiple scenarios and ensure that the target location is reached in a timely, accurate, and safe manner.